Lung ultrasound in diagnosing pneumonia in the emergency department: a systematic review and meta-analysis. (October 2018) - Orso, Daniele; Guglielmo, Nicola; Copetti, Roberto
Abstract : Community-acquired pneumonia (CAP) is one of the most widespread and severe infectious diseases worldwide. In the emergency department (ED), there is still a need for a rapid and accurate tool that can diagnose CAP. Lung ultrasound (LUS) is a recent tool that is increasingly being for this purpose. So far, the LUS has been evaluated on a wide range of patients, but not yet on the specific population in the ED through a meta-analysis. Our aim was to assess the accuracy of the LUS in diagnosing CAP in this setting through a systematic review and a meta-analysis. A systematic research of literature was carried out for all published studies comparing the diagnostic accuracy of the LUS against chest radiography or computerized tomography scan in patients older than 18 years of age with clinical criteria for CAP assessed in the ED. We extracted the descriptive and quantitative data from eligible studies, and calculated the pooled sensitivity, specificity, and diagnostic odds ratio. We defined the summary receiver operating characteristic curve. Our initial search strategy yielded 10 377 studies, of which 17 (0.2%) were eligible. These studies provided a combined sample size of 5108 participants. The general risk of bias of the considered studies was quite low, but some concerns were highlighted. The diagnostic odds ratio was around 181 ( I 2 : 27%). The pooled area under the curve, sensitivity, and specificity were, respectively, 97, 92, and 93%. The LUS was found to be an accurate tool in diagnosing CAP in adult patients in the ED. More methodologically rigorous trials are needed. Abstract : Supplemental Digital Content is available in the text.